Dynamic Simulation Analysis of Track Tension and the Influencing Factors of Deep-Sea Tracked Mining Vehicle - Fan Beibei; Liao Naixing (Shock and Vibration)
The deep-sea mining miner requires good passability to operate in complex and changeable terrain environment of the seabed. Among them, the track tension is an important factor to ensure the normal running of the vehicle. Aiming at the complex track tension problem on track link, the forces on each component of the tracked system were analyzed, and the theoretical formulas of track tension were established. The theoretical estimation and dynamic simulation of track tension in uniform speed were carried out by using the multibody dynamics model of the tracked vehicle, and the rationality of the theoretical estimation formula was verified. The influencing factors of track tension also were analyzed, and the significance of each factor on track was discussed by dynamic simulation. The results provided a theoretical basis for design of tracked vehicles.